Fiscal and monetary policy in the enlarged European Union - Sabina Pogorelec (European Central Bank (ECB), 2006)
I build a quantitative two-country DSGE model of the European Union (EU) and investigate whether there are welfare gains from fiscal policy cooperation between the new EU members and the euro area (EMU). Fiscal cooperation is defined in terms of joint maximization of the weighted average of households' welfare. I find that fiscal policy cooperation is welfare-reducing for both groups of countries. This result depends on a realistic assumption about the presence of foreign ownership of firms in the new EU countries. When there is no foreign ownership in the new EU countries, the euro area is indifferent between cooperating and not cooperating, but the new EU members still prefer not to cooperate with EMU in terms of fiscal policy.
Keywords: E63; F42; 330; Central and Eastern European Countries; Enlarged European Union; Fiscal policy cooperation; Fiscal-monetary interactions; Foreign ownership of firms; Finanzpolitik; Geldpolitik; Auslandsinvestition; Eurozone; EU-Staaten; EU-Mitgliedschaft